Omalizumab for Idiopathic Nonhistaminergic Angioedema: Evidence for Efficacy in 2 Patients. (22nd July 2018) - Brunetta, Enrico; Shiffer, Dana; Folci, Marco; Achenza, Maria I. S.; Puggioni, Francesca; Heffler, Enrico; Furlan, Raffaello; Canonica, Giorgio W.
Abstract : Presently, there is inconclusive evidence regarding the most effective treatment for idiopathic nonhistaminergic acquired angioedema (InH-AAE). Omalizumab may, however, prove to be a promising option. This case report describes two patients who presented with recurrent angioedema attacks, which was refractory to antihistamine therapy. Hence, they were treated with 300 mg omalizumab, every 4 weeks, for a period of 6 months. Both patients had shown a rapid response to the treatment and achieved complete resolution of symptoms without further AE attacks throughout the entire duration of the treatment period. After omalizumab's suspension, one patient remained symptom free for the following 6 months and the other patient had recurrence of symptoms after 2 months for which he was retreated with omalizumab and once again became symptom free. Although omalizumab seems to be effective as a prophylactic treatment for InH-AAE, the determining factors leading to the differences in time-to-relapse between patients after its suspension remain unclear. Further studies are needed in order to better determine the potential therapeutic application of omalizumab and its role in maintenance therapy.